Innovation in Strategy for Public Policy - Basu Choudhury S.; Garani S. (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
As per the World Bank, health, education and employment are the pillars of economic development. In this study, parameters are chosen in a way that covers all the areas and spheres of economic growth. Several international economic policies and theories will be studied to understand whether those can be applicable in the present scenario. Special attention to be made on fiscal and monetary policy which of govt. has been taken as part of public policy. Research demonstrated the economy’s extreme parameters in 3- dimensional space (nudge) and identified several public policies that can be implemented. But in reality, extreme conditions on all three dimensions generally do not sustain. Economics can be analysed in the following dimension: a. Macroeconomic factor: GDP deflator, CPI, WPI, FDI, continental labour transition, budget allocation v/s actual expenditure b. Micro-economic factor: supply and demand mechanism, fiscal policy, monetary policy Machine recommended public policy will be compared with man-recommended public policy based on parameters like accuracy, feasibility, effectiveness, efficiency, biasness, etc. This study will make a relative analysis of two mode of public policy recommendation.